Nations and Nationalism since 1780 / Programme, Myth, Reality - Hobsbawm J. E (Cambridge University Press, 1994)
Recent Events in Eastern Europe and the Soviet republics have since reinforced the central importance of nationalism in the history of political evolution and upheaval. Preface, Introduction, The Nation as Novelty: From Revolution to Liberalism, Popular Proto-Nationalism, The Government Perspective, The Transformation of Nationalism 1870-1918, The Apogee of Nationalism 1918-1950, Nationalism in the Late Twentieth Century, Maps, National Conflicts and Frontier Disputes 1919-1934, Source: The Times Concise Atlas of World History, Peoples and Languages and Political Divisions in the Nineteenth Century: The East European Linguistic Jigsaw, Source: The Times Concise Atlas of World History, Nationalities of the Habsburg Empire c. 1910 Source: The Penguin Atlas of World History, Index.